The State of Digital Transformation Among Indonesian SMEs: Insights from a Systematic Review - Indra Muis (Jurnal Ilmu Multidisiplin, 2025)
This study aims to systematically review the existing body of literature on digital transformation practices among small and medium enterprises (SMEs) in Indonesia. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, we identified, screened, and analysed peer-reviewed journal articles published between 2020 and 2024 from the Scopus database. The review explores the key drivers, enablers, barriers, and outcomes of digital transformation in the context of Indonesian SMEs across various sectors. Findings reveal that government support, digital literacy, and access to affordable digital infrastructure play a significant role in accelerating digital adoption. Conversely, limited financial resources, resistance to change, and low technological readiness remain critical challenges. The study also highlights emerging trends such as the use of cloud computing, e-commerce platforms, and Industry 4.0 technologies as transformative tools for improving competitiveness and operational efficiency. This review contributes to the academic understanding of digitalization in developing economies and offers practical insights for policymakers, business leaders, and researchers aiming to support Indonesia's digital economy agenda. Future research directions are proposed to address gaps in longitudinal studies, sector-specific analysis, and the role of digital ecosystems in SME transformation.